Kinetics of the Ruthenium(III) and Palladium(II) Catalysed Polymerization of Methylmethacrylate by Aminoalcohols in Presence of CCI4 - Pachauri, Manisha; Srivatave, Pankaj; K. Upadhyay, Santosh (Asian Journal of Chemistry, 2010)
Ruthenium(III) and palladium(II) catalysed polymerization of methylmethacrylate (MMA) with aminoalcohols, viz., ethanolamine (EA) and diethanolamine (DEA) has been studied in presence of CCl4 and in dimethylsulfoxide (DMSO) medium by employing a dilatometric technique at. 60°C. The rate of polymerization (Rp ) of MMA is proportional to [MMA], [Aminoalcohol]1/2, [CCl4]1/2 and {k' + k"[Catalyst]1/2}, where k' and k" are rate constants for uncatalysed and catalysed path of polymerization respectively. At higher CCl4 concentration when [CCI4]/[Aminoalcohols] > 1, the rate of polymerization becomes independent of [CCI4]. The rate of polymerization is inhibited by hydroquinone, suggesting a free radical mechanism. Mechanism involving the charge-transfer complex between Aminoalcohol-Catalyst complex and CCI4 has been suggested for the initiation of polymerization of Methylmethacrylate.